2008
DOI: 10.1080/13674580802264803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuing professional development on group work practices in Scottish primary schools

Abstract: Keywords: group work, primary school, continuing professional development for teachers Word count=6729Journal of In-service Education (accepted for publication in second half of 2008)-2 -Effects of continuing professional development on group work practices in Scottish primary schools ABSTRACT This study investigated the effects of a continuing professional development (CPD) initiative that provided collaborative group work skills training for primary school teachers. The study collected data from 24 primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Whilst teachers are used to making professional judgements of the levels that students are working at, the inter-rater reliability of such judgements remains a potential source of error. Having said this it should be noted that previous studies have reported that teacher judgement correlated highly with students' performance in standardised tests (Thurston, Christie, Howe, Tolmie, & Topping, 2008). Future research should address this issue and look at relationships between aspects of wellbeing and student performance in standardised tests.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst teachers are used to making professional judgements of the levels that students are working at, the inter-rater reliability of such judgements remains a potential source of error. Having said this it should be noted that previous studies have reported that teacher judgement correlated highly with students' performance in standardised tests (Thurston, Christie, Howe, Tolmie, & Topping, 2008). Future research should address this issue and look at relationships between aspects of wellbeing and student performance in standardised tests.…”
Section: Discussionmentioning
confidence: 99%
“…International research provides information how the lack of conception about teacher professional development influences teaching and learning process and teachers leaving the profession (Harford, 2010;Collinson et al, 2009;Thurston et al, 2008;Latham & Vogt, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Starptautiskie pētījumi sniedz informāciju par to, ka koncepcijas trūkums pedagogu tālākizglītībā būtiski ietekmē mācībumācīšanās procesu un pedagogu aiziešanu no profesijas (Harford, 2010;Collinson et al, 2009;Thurston et al, 2008;Latham & Vogt, 2007). Lai virzītos uz iekļaujošo izglītību, pedagogiem ir jāsaprot vispirms pašiem sevi, savas vērtības, bet attiecībā uz izglītojamiem, jābūt izpratnei par viņu vispārīgajām, specifiskajām un individuālajām vajadzībām (Rodriguez, 2010).…”
Section: Problēmas Teorētiskais Pamatojums Theoretical Background Of unclassified
“…Many of the previous studies conducted in the literature also support this view. In the researches carried out by Doymuş et al (2004), Baines et al (2007), Kıncal et al (2007), Şenol et al (2007), Bozkurt et al (2008), Thurston et al (2008), Gök et al (2009), Ajaja and Eravwoke (2010), Aksoy and Gürbüz (2012), Ebrahim (2012), Parveen and Batool (2012), Kozcu Çakır et al (2013) and Meder (2014) it has been determined that students learning in cooperation positively affects their success in science lessons.…”
Section: Discussionmentioning
confidence: 99%